2014
DOI: 10.1042/bj20130924
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/S100 proteins inhibit the interaction of FKBP38 with Bcl-2 and Hsp90

Abstract: FKBP38 (FK506-binding protein 38), a membrane-anchored TPR (tetratricopeptide repeat)-containing immunophilin, regulates signalling pathways such as cell survival, apoptosis, proliferation and metastasis. However, the mechanisms that regulate the activity of FKBP38 are, at present, poorly understood. We previously reported that Ca2+/S100 proteins directly associate with the TPR proteins, such as Hop [Hsp70 (heat-shock protein of 70 kDa)/Hsp90-organizing protein], kinesin-light chain, Tom70 (translocase of oute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Based on published literature, the pathway building analysis predicted the interconnection among all genes utilized for the analysis. For instance, the analysis projected that upregulation of the calcium binding protein S100P leads to downregulation of Bcl‐2 (Shimamoto et al., 2014), which we found to be true when mifepristone induced cell death in combination with PI3K inhibitors (Wempe et al., 2013). S100P is predicted to increase expression of ezrin, which is confirmed in our results in SKOV‐3 cells (see Table S6).…”
Section: Discussionmentioning
confidence: 86%
“…Based on published literature, the pathway building analysis predicted the interconnection among all genes utilized for the analysis. For instance, the analysis projected that upregulation of the calcium binding protein S100P leads to downregulation of Bcl‐2 (Shimamoto et al., 2014), which we found to be true when mifepristone induced cell death in combination with PI3K inhibitors (Wempe et al., 2013). S100P is predicted to increase expression of ezrin, which is confirmed in our results in SKOV‐3 cells (see Table S6).…”
Section: Discussionmentioning
confidence: 86%
“…Several studies have demonstrated that Ca 2+ ‐S100 proteins (S100A2, S100P, S100A6, S100A12, S100A1) associate with tetratricopeptide repeat (TPR)‐containing proteins (Shimamoto et al ., , , , ; Yamaguchi et al ., ; Maciejewski et al ., ). TPR‐containing proteins mediate protein–protein interactions and participate in the ordered assembly of heat shock proteins (HSP) HSP70–HSP90 into multichaperone complexes with their client proteins (Blatch & Lassle, ; Scheufler et al ., ).…”
Section: S100b Involvement In Adaptive Cellular Stress Responsesmentioning
confidence: 99%
“…Intracellularly, S100B, as a calcium-sensor protein, appears to regulate a variety of activities, transferring signals from second messengers and interacting with different molecules in different cell types. In particular, S100B intervenes in cell proliferation, survival and differentiation (Baudier et al 1992;Millward et al 1998;Arcuri et al 2005;Raponi et al 2007;Saito et al 2007;Riuzzi et al 2011;Shimamoto et al 2014;Li et al 2016), participates in the regulation of cellular calcium homeostasis and enzyme activities (Zimmer and Van Eldik 1986;Heierhorst et al 1996;Pozdnyakov et al 1997;Xiong et al 2000;Gentil et al 2001;Brozzi et al 2009;Tsoporis et al 2009;Wen et al 2012;Agam and Almong 2015;Gogl et al 2016) and even interacts with the cytoskeleton (Baudier and Cole 1988;Donato 1988;Skripnikova and Gusev 1989;Mbele et al 2002), but data currently available do not appear to converge toward a clearly defined function. In contrast, there is mounting evidence indicating an increasingly clearer role for extracellular S100B.…”
mentioning
confidence: 99%